Survey of Assessment Techniques for Religious and Moral Values in Early Childhood in Baruga Sub-district, Kendari City - Andreas Putra, Aris Try; Anhusadar, Laode (EduBasic Journal: Jurnal Pendidikan Dasar, 2025)
Analysis of current assessment practices is crucial to evaluate holistic development of religious and moral values in children from an early age. The purpose of this study was to analyze the implementation of assessment techniques for the development of religious and moral values in early childhood. This study employed a quantitative approach using a survey method conducted in four urban villages in Baruga Sub-district, Kendari City, involving 20 Kindergarten or Raudhatul Athfal teachers recruited through proportional random sampling. The results revealed that 95% of teachers used assessment techniques to evaluate the religious and moral development of children, with direct observation being the most common method. Additionally, 90% of teachers have used rubrics and parental involvement stood at 85%, highlighting the need for improved communication. Moreover, 90% of teachers conducted daily assessments, provided regular feedback, and recorded the results in writing, with daily notes being the predominant documentation method. However, the use of portfolios remained low at 5%. It concludes that early childhood educators are committed to assessing children's religious and moral development through suitable technique, with high parental involvement and frequent assessments demonstrating the importance of continuous monitoring. Nevertheless, the limited use of portfolios suggests that some assessment tools are underutilized, which may limit the comprehensiveness of documentation. It also implies that early childhood educators require continuous professional development to enhance and diversify assessment methods, foster school-parent collaboration, and secure necessary assessments training and resources.